The transit passage regime under international law and its impact on the straits states powers : a case study on the straits of Malacca / Dr. Musrifah Sapardi Rustam - Sapardi Rustam, Musrifah (Faculty of Administratron and Law, 2001)
Significant questions of control over navigation by foreign shipping only arise in those straits used for international navigation which cannot be traversed without entering the territorial waters of straits States, as in the case of the Straits of Malacca. The law relating to straits used for international navigation therefore became more important as States increasingly claimed 12 miles territorial seas.3 The Third United Nations on the Law of the Sea Convention (1982 LOSC) introduced the new regime.